Crystal structure and electrical properties of bismuth sodium titanate zirconate ceramics - Ampika Rachakom (2018)
Lead-free bismuth sodium titanate zirconate (Bi0.5Na0.5Ti1-xZrxO3where x = 0.20, 0.35, 0.40, 0.45, 0.60, and 0.80 mole fraction) [BNTZ] ceramics were successfully prepared using the conventional mixed-oxide method. The samples were sintered for 2 h at temperatures lower than 1,000°C. The density of the BNTZ samples was at least 95% of the theoretical values. The scanning electron microscopy micrographs showed that small grains were embedded between large grains, causing a relatively wide grain size distribution. The density and grain size increased with increasing Zr concentration. A peak shift in X-ray diffraction patterns as well as the disappearance of several hkl reflections indicated some significant crystal-structure changes in these materials. Preliminary crystal-structure analysis indicated the existence of phase transition from a rhombohedral to an orthorhombic structure. The dielectric and ferroelectric properties were also found to correlate well with the observed phase transition. © 2012 Rachakom et al.